Arab representation in Israeli healthcare professions: achievements, challenges and opportunities - Bruce Rosen; Sami Miaari (Israel Journal of Health Policy Research)
Abstract Background Israel is a multiethnic society with a population of 9.8 million at the end of 2023. Israeli Arabs (i.e., Arab Palestinian citizens of Israel) account for 21% of the Israel’s overall population, 22% of its working age population and 16% of the employed population. This study has several objectives: (1) To provide an overview of the current representation of Israeli Arabs in four key health care professions (medicine, nursing, dentistry, and pharmacy) in terms of employment, licensure, and professional studies; (2) To document changes in those parameters over the past decade, subject to limitations of data availability; (3) To provide a broader context on the employment of Israeli Arabs; (4) To explore the policy implications of the key findings. Methods Estimates of employment levels are based on the Labor Force Survey (LFS) of the Central Bureau of Statistics (CBS). Data on licensure (i.e., professional qualification) and place of professional studies were extracted from the Ministry of Health report series entitled “The Health Care Professions”. Data on enrollment in degree programs in Israel was provided by the Council of Higher Education. Important background information was elicited from relevant policy documents and policy experts. Results In 2023, among employed Israelis up to age 67, Arabs constituted approximately one-quarter of Israel’s physicians (25%), nurses (27%), and dentists (27%), and half of Israel’s pharmacists (49%). These percentages are substantially higher than they were in 2010, with the increase being particularly marked in the case of physicians (25% versus 8%). The number of new licenses granted annually increased significantly between 2010 and 2022 for both Arabs and Jews in each of the professions covered. The percentage of newly licensed professionals who are Arab increased substantially among physicians and nurses, while remaining stable among dentists and pharmacists. In medicine, dentistry, and pharmacy, many of the licensed Arab health professionals had studied outside of Israel; this phenomenon also exists for nursing but is less widespread there. In the 2022/3 academic year, the percentage of first-degree students in Israeli colleges and universities who were Arab was 70% in pharmacy, 33% in nursing, 23% in dentistry, and 9% in medicine. Between 2012/3 and 2022/3 the percentage of first-degree students who are Arab increased substantially for pharmacy, declined slightly for nursing, and declined substantially for medicine and dentistry. Conclusions Arab professionals play a substantial and recently increased role in the provision of health care services in Israel. It is important to recognize, appreciate, and maintain this substantial role. Moreover, its potential as a model for sectors other than health care should be explored. To build on achievements to date, and to promote continued progress, policymakers should expand access to health professional education within Israel, upgrade the skills of graduates of non-Israeli universities, promote diversity in leadership positions and key specialties, and expand specialty care services in Arab localities.